The Impact of Financial Factors on Financial Distress in Life Insurance Companies: The Moderating Role of ESG - Firdaus, Muhammad; Endri, Endri (International Journal of Economics and Financial Issues, 2025)
The study aims to examine the influence of financial factors, consisting of: Leverage (DAR), Insurance Claims (KA), Liquidity (CR), Risk-Based Capital (RBC), and Sales Growth (SG) on Financial Distress (FD) with the role of Environmental, Social, and Governance (ESG) as a moderating variable. The study was conducted on insurance sector companies registered with the Indonesian Financial Services Authority (OJK) from 2020 to 2023. This study used a panel data regression method on 26 selected insurance companies. The results of the study from the model without the role of moderating variables found that DAR, RBC, SG, and ESG did not affect FD. At the same time, KA and CR had a positive impact on the likelihood of insurance companies experiencing FD. Different findings were revealed in the model with the role of ESG as a moderating variable; KA was positively related to FD, and the interaction of ESG with CR strengthened its influence on the likelihood of insurance companies experiencing FD. To our knowledge, this study, which investigates the determinants of FD with the role of the moderating variable ESH in insurance companies in Indonesia, has never been studied before. Furthermore, this study provides valuable information for regulators and policymakers to improve liquidity, insurance claim payments, and ESG practices in the insurance sector.